2012
DOI: 10.1111/j.1365-2583.2012.01153.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the brain dopaminergic system by juvenile hormone in honey bee males (Apis mellifera L.)

Abstract: Dopamine (DA) and juvenile hormone (JH) are multifunctional regulators of behaviour in social insects, with distinct effects across species and even between different dominance positions within the same species. We examined the effects of JH on the brain dopaminergic system in honey bee males to investigate the potential relationship between JH and DA within Apis mellifera. Both DA content and the expression of three DA receptor genes (Amdop1, Amdop2 and Amdop3) increased in the male honey bee brain from day 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Studies in various insect species have established that JH interacts with dopamine (DA) (Woodring and Hoffmann, 1994; Sasaki et al, 2012). Past studies have also implied the existence of direct interactions between DA and JH to effect the organization of neural circuitry in Drosophila (Gruntenko et al, 2005 and 2007), consistent with observations that DA also functions to mediate ovarian development, sexual receptivity, and fertility (Neckameyer, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in various insect species have established that JH interacts with dopamine (DA) (Woodring and Hoffmann, 1994; Sasaki et al, 2012). Past studies have also implied the existence of direct interactions between DA and JH to effect the organization of neural circuitry in Drosophila (Gruntenko et al, 2005 and 2007), consistent with observations that DA also functions to mediate ovarian development, sexual receptivity, and fertility (Neckameyer, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In the cockroach P. americana , an overdose of this drug acted weakly on the receptors of other amines, such as octopamine [ 49 ]. The concentrations applied in the present experiments (32.2 nl of 100 pM or 1 nM) were much lower than those used in other insects; 1 μl of 10 mM to A. mellifera abdomen [ 50 ] and 10 μl of 20 mM to P. americana haemolymph [ 22 ]. Because these previous studies showed no evidence of antagonism of the receptors of other amines, the present drug concentrations may have little or no effect on other receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In D. melanogaster , DA may be a potent modulator to regulate JH titre by promoting the activity of the corpora allata [ 52 ]. JH–DA interactions were involved in locomotor activities and flight behaviours in male honeybees [ 30 , 50 ] and the carpenter bee Xylocopa appendiculata [ 53 ]. In Z. nevadensis , JHAMT and CYP15A1 genes involved in the final steps of JH biosynthesis were highly expressed in the heads of No.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of honeybees described a simple genetic system of haplodiploid development and showed that different diets and cell sizes determine the physiological characteristics, such as body size, behavior, physiology, and lifespan 23 , of the three castes of worker, drone, and queen bee. The relationship between honeybees behavior and the gene expressions 24 of odorant receptors 25 27 and hormones 28 , 29 in the brains of workers and queen bees were investigated in numerous studies that investigated the social aspect of bee behavior. While developing into three castes, royal jelly was revealed to trigger larvae to develop into a queen and control the gene expression of the juvenile hormone, which plays a key role in sex-determination 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%